Eight patients with inflammatory myofibroblastic tumor treated with rigid bronchoscopy - Byeong-Ho Jeong; Rong Lih Ho; Ho Yun Lee; Joungho Han; Hojoong Kim (BMC Pulmonary Medicine)
Abstract Background Pulmonary inflammatory myofibroblastic tumor (IMT) accounts for 0.04–0.7% of all lung tumors, and endobronchial IMT accounts for only 10% of all pulmonary IMTs. Little is known about the therapeutic outcomes of rigid bronchoscopy for endobronchial IMT. Here, we report a case series of eight patients with endobronchial IMT underwent rigid bronchoscopy. Methods We retrospectively analyzed eight patients with endobronchial IMT between January 2004 and December 2023. Results The median age of our patients was 36 years, and 62.5% were male. Dyspnea was the predominant symptom in cases where the tumor was centrally located (n = 6), whereas hemoptysis was the predominant symptom in peripherally located tumors (n = 2). Most cases had high contrast enhancement and a tumor stalk without bronchial wall invasion on computed tomography (CT) and bronchoscopy. Complete endoscopic resection and laser cauterization via rigid bronchoscopy were possible in five patients. There were only two cases in which tumors remained after the procedure, requiring additional treatment (chemotherapy and surgical resection, respectively). In one patient, surgical resection was performed three weeks after the procedure, and the surgical specimen was free of residual tumor. There was no mortality during the median follow-up duration of 18.8 months. Conclusions Endoscopic resection and laser cauterization using rigid bronchoscopy may serve as a safe and effective alternative treatment modality to surgery for patients with endobronchial IMT.